Cover Picture: Solution Structure of Turbo‐Hauser Base TMPMgCl⋅LiCl in [D8]THF (Chem. Eur. J. 36/2016). Issue 36 (14th July 2016) - Neufeld, Roman; Stalke, Dietmar
Abstract : Boosted by LiCl addition, the turbo‐Hauser base, TMPMgCl⋅LiCl, contains a trigonal coordinated magnesium atom providing outstanding reactivity and selectivity. ECC DOSY NMR spectroscopy confirms the structure in solution. More information can be found in the Communication by D. Stalke and R. Neufeld onpage 12624 .